A comprehensive study on microstructure, in-vitro biodegradability, bacterial sensitivity, and cellular interactions of novel ternary Zn-Cu-xAg alloys for urological applications - Yilmazer, H.; Basit, S.; Sen, A.; Yilmazer, Y.; Dalbayrak, B.; Arisan, E. D.; Arisan, S.; Islamgaliev, R. K.; Dikici, B. (ELSEVIER SCIENCE SA, 2023)
Novel ternary Zn-Cu-xAg alloys are designed and fabricated by the casting method under a vacuum atmosphere and then homogenized at 350 degrees C for 15 h. The effect of Ag concentration (x: 0, 1, 2, 3, and 4 wt%) on microstructure, hardness, in vitro corrosion, biodegradability, and bacterial sensitivity was studied systematically. The structural analysis of the alloys was investigated by using a scanning electron microscope (SEM-EDS), and an optical microscope (OM). Besides, phase characterization of the samples was conducted using X-ray diffraction (XRD). The degradation behaviors of the alloys were determined under in vitro conditions, electrochemical polarization, and immersion tests (up to 21 days) in artificial urine (AU) solution. The maximum hardness value for Zn-1Cu-4Ag alloy was about 2.38 times higher than pure Zn due to solid-solution strengthening and precipitation hardening of (Ag, Cu)Zn-4 phases. The highest and lowest I-corr values, reference also corrosion rate, were calculated in Zn-1Cu and Zn-1Cu-3Ag alloys as 17.13 and 1.318 mA center dot cm(-2), respectively. The alloys' bacterial sensitivities were evaluated with the disc diffusion test for E. coli and S. aureus. The inhibition ratio of the Zn-1Cu-1Ag was higher than the inhibition rates of the other alloys on E. coli and S. aureus. In addition, the biological properties of the generated material were promising by altering cell survival/death ratio in both prostate epithelial and bladder cancer cells related to their use potential in urology.
Keywords: Bioabsorbable; Zn-Cu-Ag alloy; Urological devices; Degradation; In-vitro corrosion; Cell culture; MECHANICAL-PROPERTIES; DEGRADATION BEHAVIOR; CORROSION BEHAVIOR; MAGNESIUM ALLOYS; SILVER NANOPARTICLES; MG; DESIGN; BIOCOMPATIBILITY; CYTOTOXICITY; METALS; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering